Didactic Potential of an Electronic Textbook for Improving Speaking Skills at Foreign Language Classes (Proceedings of Southern Federal University. Philology, 2021)
Yulia M. Orekhova (Yaroslavl, Russian Federation)An important aim of higher education intuitions of our country is creating of electronic educational system. Informatization of education has influenced all subjects, including foreign languages. The integration of digital technologies into the teaching process and production of multimedia electronic textbooks are the principal directions of modernization of language education.The paper aims to prove the high didactic potential of an electronic textbook on the subject “Foreign language” for development students’ communicative competence by means of analyzing of Russian and foreign authors’ scientific researches, development of electronic textbook and its use at foreign language classes.A detailed list of the lesson objective which can be solved by means of an electronic textbook on the subject “Foreign language” is given in the present article. The necessity of inclusion the digital products in the process of teaching foreign languages is also proved. The appropriateness of its use for development students’ communicative skills is justified. The list of speaking skills developed by means of electronic text book is. The examples of tasks for individual and group work are given too.The possibility of using the electronic textbook “French language for adjuncts” for the complex formation of speaking skills in oral and written communication is also shown. The necessity of its inclusion into the program of linguistic education at university is proved.Key words: foreign language, foreign language communicative competence, electronic textbook, Federal Educational Standard, speaking skills, examples of tasks.DOI 10.18522/1995-0640-2021-2-205-213